Electronic Structure of Mg-, Si-, and Zn-Doped SnO2 Nanowires: Predictions from First Principles - Platonenko, Alexander; Piskunov, Sergei; Yang, Thomas C.-K.; Juodkazyte, Jurga; Isakoviča, Inta; Popov, Anatoli I.; Junisbekova, Diana; Baimukhanov, Zein; Dauletbekova, Alma (MDPI, 2024)
We investigated the electronic structure of Mg-, Si-, and Zn-doped four-faceted [001]- and [110]-oriented SnO2 nanowires using first-principles calculations based on the linear combination of atomic orbitals (LCAO) method. This approach, employing atomic-centered Gaussian-type functions as a basis set, was combined with hybrid density functional theory (DFT). Our results show qualitative agreement in predicting the formation of stable point defects due to atom substitutions on the surface of the SnO2 nanowire. Doping induces substantial atomic relaxation in the nanowires, changes in the covalency of the dopant–oxygen bond, and additional charge redistribution between the dopant and nanowire. Furthermore, our calculations reveal a narrowing of the band gap resulting from the emergence of midgap states induced by the incorporated defects. This study provides insights into the altered electronic properties caused by Mg, Si, and Zn doping, contributing to the further design of SnO2 nanowires for advanced electronic, optoelectronic, photovoltaic, and photocatalytic applications. © 2024 by the authors. --//-- This is an open access article Platonenko, A.; Piskunov, S.; Yang, T.C.-K.; Juodkazyte, J.; Isakoviča, I.; Popov, A.I.; Junisbekova, D.; Baimukhanov, Z.; Dauletbekova, A. Electronic Structure of Mg-, Si-, and Zn-Doped SnO2 Nanowires: Predictions from First Principles. Materials 2024, 17, 2193. https://doi.org/10.3390/ma17102193 published under the CC BY 4.0 licence.
This research was funded by the Ministry of Education and Science of the Republic of Kazakhstan, grant number AP14871479 \u201CTemplate synthesis and experimental-theoretical study of a new type of heterostructures for nano and optoelectronic applications\u201D. S.P., I.I., J.J. and T.C.-K.Y. are also thankful for financial support from the M-ERA.NET project \u201CMultiscale computer modelling, synthesis and rational design of photo(electro)catalysts for efficient visible-light-driven seawater splitting\u201D (CatWatSplit). This work was also supported in part by HORIZON 2020 RISE-RADON Project \u201CIrradiation driven nanofabrication: computational modelling versus experiment\u201D (A.P. and A.I.P.). Calculations of electronic properties were performed on the Latvian Supercomputer Cluster (LASC) located at Institute of Solid State Physics in Riga. The Institute of Solid State Physics, University of Latvia, as a Center of Excellence, has received funding from the European Union\u2019s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; ab initio calculation; density functional theory; doped nanowires; electronic structure; SnO2